2019
DOI: 10.1128/msystems.00337-18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Metagenomic Prediction of the Metaproteome in a 4.5-Year Study of a Patient with Crohn's Disease

Abstract: A majority of current microbiome research relies heavily on DNA analysis. However, as the field moves toward understanding the microbial functions related to healthy and disease states, it is critical to evaluate how changes in DNA relate to changes in proteins, which are functional units of the genome. This study tracked the abundance of genes and proteins as they fluctuated during various inflammatory states in a 4.5-year study of a patient with colonic Crohn’s disease. Our results indicate that despite a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 83 publications
5
55
0
Order By: Relevance
“…Future efforts could be aimed at incorporating co-culture of host cells/tissue and gut bacteria [5153] into a high-throughput drug screening process for achieving more comprehensive insights on host-drug-microbiome interaction. Metaproteomics is a tool that is orthogonal to other omics technologies [17], hence for the need of deeper investigations, RapidAIM could also be coupled with techniques such as metagenomics or metabolomics for a multiple dimension view of the microbiome interaction with drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future efforts could be aimed at incorporating co-culture of host cells/tissue and gut bacteria [5153] into a high-throughput drug screening process for achieving more comprehensive insights on host-drug-microbiome interaction. Metaproteomics is a tool that is orthogonal to other omics technologies [17], hence for the need of deeper investigations, RapidAIM could also be coupled with techniques such as metagenomics or metabolomics for a multiple dimension view of the microbiome interaction with drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is little insight on which microbial traits actually contribute to the functional activities of the microbiome, as functions predicted from 16S rDNA or metagenomics analyses are not necessarily expressed. Studies have shown that gene copy numbers are not representative of protein levels [17]. In addition, RNA expression have limited correlation to the actual protein abundance [18].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we observed over 5,600 proteins that that could hold new biological insights into the impact of dietary fiber versus fermented foods. While this identification depth is greater than some of the first reported metaproteomic searches on stool, newer studies have reported substantially more host and microbial protein identifications (53,000 total proteins, various biological matrices) 9,17,21 . We attribute the decreased number of identifications in our current study to several factors.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, we suspect many low-abundant, sample-specific host and microbial proteins were not identified. To combat this, future iterations of SHT-Pro could incorporate peptide fractionation and longer mass spectrometry runs per sample, which has been shown to significantly increase identification of low-abundant host and microbial proteins 9 . In this context, striking a balance between throughput and proteomic depth is crucial, as the biological and health-related significance of low-abundance proteins remains promising but unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation